Gender Trends Perspective: Representation of Women in the Political Sphere - et. al., Subhan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The introduction to this problem is the issue of women's representation in regional legislatures and political parties, whose attainment is still not as desired. It is no longer possible for women to represent 30% of women's representation by simply relying on the commitment of political parties and government policies. This research aims to describe the quality of gender equality in politics and women's situation in politics. The theory used is Gender Trends. This research method is descriptive qualitative with sustainable analysis and literature studies. The research results revealed women's opportunities in pushing women's political expectations. There is still a minimal number of women in the regional legislature, which impacts the ability to voice women's interests to be limited. With quality playing a major role in gender equality in the political realm, it is not only about the fulfillment of the number of women involved in political activities but also a statutory provision that must be fulfilled by every political party to provide opportunities for women's representation in their activities in the political realm.